Kegiatan Mewarnai dalam Mengembangkan Keterampilan Motorik Halus Anak Sekolah Dasar Kelas Awal Melalui Bimbel Tambahan: Pengabdian - Annisa Qomariah; Reni Ardiana; Nurdin Arifin; Rini Fitriyani; Carolina Octavia (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This community service aims to develop the fine motor skills of early grade elementary school children through coloring activities in the form of additional tutoring. Fine motor skills, which involve the ability to use small muscles in the hands and fingers, are essential for children's success in various daily activities, including writing, drawing, and using stationery. The results of the community service show that after participating in the coloring activities, most children experienced significant improvements in their fine motor skills. The assistance provided by the facilitator provided clear directions regarding coloring techniques, so that children could improve their accuracy and precision in drawing and coloring. This activity also succeeded in reducing children's dependence on technology and improving their social skills, such as working together with friends. Therefore, this activity not only supports the development of fine motor skills but also contributes to children's social and emotional development.